Harnessing the Power of Technology to Enhance Language Learning and Development - Almestareehi Kefah Mohammad (Taez University, 2023)
Technology has revolutionized the way we learn and develop language. With the use of technology, it has become easier than ever to learn and develop a new language. Technology has enabled us to access a wealth of language resources, such as online courses, tutorials, apps, and interactive websites. Harnessing the power of technology to enhance language learning and development has become increasingly prevalent in recent years. This abstract explores the central concept of using digital tools and resources to supplement traditional language learning methods. It highlights the various ways technology can improve language learning outcomes, including interactive learning platforms, online courses and tutorials, language learning apps, virtual reality and augmented reality, language exchange platforms, online resources, and adaptive learning systems. The abstract emphasizes the importance of technology as a complement to traditional instruction, providing increased accessibility, interactivity, personalization, and immersion in language learning. It concludes by highlighting the need for human interaction and guidance in conjunction with technology to maximize language learning and development. In this article, we will look at how technology can be used to enhance language learning and development. We will discuss the benefits of using technology in language learning, the role of technology in language learning, how to create a technology-based learning environment, and what challenges may arise when using technology-based language learning.